Consistent analyses for determination of the point-nucleon distributions by electron and proton scattering - Suzuki, Toshio; Danjo, Rika; Suda, Toshimi; Matsuzaki, Masayuki; Wakasa, Tomotsugu (Frontiers in Physics, 2025)
Electron scattering cross section, as well as proton scattering cross section, observes the point-proton and the point-neutron distributions, ρτ(r),(τ=p,n), but both cross sections are not able to determine them separately. If they are analyzed consistently with each other, there is a possibility to determine them with less ambiguity. The consistency can be examined through the moments of the charge distribution, ρc(r), which linearly depend on the moments of the point-proton and -neutron distributions, ρτ(r), (τ=p,n). The fourth moment, ⟨ r4 ⟩c, of ρc(r) in 208Pb observed in electron scattering is well-reproduced by the mean square radii, ⟨ r2 ⟩τ, of ρτ(r) obtained consistently in the non-relativistic analyses of electron and proton scattering cross sections. The regression analyses of the non-relativistic mean-field models reproduce well those values of the moments.